Een irenische dialoog met Wim Weren over geweld in Johannes 7:53-8:11 - Verheyden, Joseph (HTS teologiese studies, 2008)
An irenic dialogue with Wim Weren about violence in John 7:53-8:11 This essay engages in a dialogue with Wim Weren’s contribution in this volume. It first discusses some hermeneutical perspectives on violence in the pericope on the adulteress woman in John 7:53-8:11. It then discusses the use of Deuteronomy in this passage against the background of Jesus’ radical new perspective on violence.